2014
DOI: 10.1186/preaccept-1633779014133168
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of severe infections associated with anti-epidermal growth factor receptor monoclonal antibodies in cancer patients: a systematic review and meta-analysis

Abstract: Background: Anti-epidermal growth factor receptor (EGFR)-monoclonal antibodies (MoAbs) have been widely used in a variety of malignancies. Severe infections (≥grade 3) are potentially life-threatening adverse events with these drugs. However, the contribution of anti-EGFR MoAbs to infections is still unknown. We performed this meta-analysis to determine the overall incidence and risk of severe infections in cancer patients treated with these drugs. Methods: The databases of PubMed and abstracts presented at on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Rafailidis et al [42] conducted the first systematic review in 2007 and demonstrated that there was an increased risk of developing monoclonal antibodies related severe infections but not for fatal adverse events. In consistent with previous results, two later meta-analyses also showed that EGFR-monoclonal antibodies significantly increased the risk of developing severe infections but not for fatal adverse events [16, 43]. Recently, Qi et al performed another meta-analysis and showed that there was an increased risk of developing all-grade (RR 1.45, p < 0.001) and high-grade (RR 1.59, p < 0.001) infectious events in cancer patients treated with bevacizumab [44].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Rafailidis et al [42] conducted the first systematic review in 2007 and demonstrated that there was an increased risk of developing monoclonal antibodies related severe infections but not for fatal adverse events. In consistent with previous results, two later meta-analyses also showed that EGFR-monoclonal antibodies significantly increased the risk of developing severe infections but not for fatal adverse events [16, 43]. Recently, Qi et al performed another meta-analysis and showed that there was an increased risk of developing all-grade (RR 1.45, p < 0.001) and high-grade (RR 1.59, p < 0.001) infectious events in cancer patients treated with bevacizumab [44].…”
Section: Discussionsupporting
confidence: 88%
“…Infections have been reported with anti-EGFR agents. In 2014, Qi et al performed a meta-analysis and found a significantly increased risk of severe infectious events associated with the use of anti-EGFR mono-clonal antibodies cetuximab and panitumumab in cancer patients (RR 1.34, p = 0.003) [16]. However, whether EGFR-TKIs increase the risk of infections in NSCLC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread availability and clinical use of EGFR inhibitors as anti-neoplastic therapies provides future opportunities to explore the functional role of this SIRS-associated network hub in severe sepsis through direct pharmacologic targeting. Interestingly, inhibition of the EGF-EGFR axis using anti-EGFR monoclonal antibodies is associated with increased risk of severe infections in cancer patients (31), further implicating this pathway as a key regulator of host response to sepsis. Furthermore, several other network nodes identified from our analysis are druggable sites, further supporting the utility of our approach in systematically identifying new therapeutic targets in MODS (please see Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis also demonstrated that the use of anti-EGFR MoAbs significantly increased the risk of developing severe infections (RR: 1.34, 95% CI: 1.10–1.62, P =0.003) in cancer patients. More importantly, the use of anti-EGFR MoAbs significantly increased the risk of severe sepsis in cancer patients (RR: 4.30, 95% CI: 1.80–10.27, P =0.001) 37. On the basis of these findings, clinicians should pay more attention to severe infections to reduce the risk of FAEs in advanced gastric patients.…”
Section: Discussionmentioning
confidence: 94%